KEDUDUKAN IJMA SEBAGAI DALIL HUKUM TERHADAP JABATAN PUBLIK - Ashsubli, Muhammad (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2016)
Asked for office or running for political ethics are common. Some of the arguments of such consensus clearly explain how the real Islam considers an office that has become a symbol of social status. Candidacy and campaign for certain political positions can be justified under Islamic law for a person who within him there are two things. First, has the capacity, capability and acceptability sufficient to assume that he ran for office and campaign for him to reach it. Second, the main motivation is certainly solely to seek the pleasure of Allah and for the sake of realizing the public good and not for personal interests and reach or not the means to do things that are destructive to the interests of the public. Thus, through this paper hope to anyone who wants to run for leaders to be honest in judging ourselves, so that positions of leadership which it aspires into leadership, accompanied by the Lord's hand in giving the best to the people method used in this study using Quantitative Research. This study uses a measurement technique problem through careful against varaiabel-specific variables, so to be produce conclusions that can be generalized, separated from the context of the time and the situation and the type of data collected mainly quantitative data. Quantitative research is used primarily to develop the theory in a scientific discipline. Use of taking the measurements with analyzes statically in research implies that this study uses quantitative methods.